The effect of dynamic recrystallisation on the rheology and microstructures of partially molten rocks. (January 2019) - Llorens, Maria-Gema; Gomez-Rivas, Enrique; Ganzhorn, Anne-Céline; Griera, Albert; Steinbach, Florian; Roessiger, Jens; Labrousse, Loic; Walte, Nicolas P.; Weikusat, Ilka; Bons, Paul D.
Abstract: The present study is based on a series of two-dimensional simple shear numerical simulations of two-phase non-linear viscous materials used to investigate the mechanical behaviour of two-phase aggregates representing partially molten rocks. These simulations couple viscoplastic deformation with dynamic recrystallisation ( DRX ). The aim of these simulations is to investigate the competition between deformation and recrystallisation, and how they affect the mechanical behaviour and resulting microstructures of the deforming material. We systematically vary the melt to solid rock ratio, the dihedral angle of melt and the ratio of DRX vs. deformation. The results show that the amount of DRX and the dihedral angle have a first-order impact on the bulk rheology and the melt distribution in the aggregate. The numerical results allow defining two regimes, depending on the relative contribution of deformation and DRX : (1) a deformation-dominated regime at high strain rates ( i.e., with a low ratio of recrystallisation vs. viscoplastic deformation) and (2) a recrystallisation-dominated regime at low strain rates ( i.e., with a high ratio of recrystallisation vs. viscoplastic deformation). The first case results in systems bearing large connected melt pockets whose viscous flow controls the deformation of the aggregate, while disconnected smaller melt pockets develop in models where dynamic recrystallisation dominates. The results of this study allow us to better understand the development of connected melt pockets, which may focus melt flow. The distribution of the melt phase plays a key role in the formation of larger-scale melt-enriched shear bands, which in turn has a direct influence on large-scale convective mantle flow. Highlights: Simple shear simulations of two-phase non-linear viscous aggregates are presented. We investigate the competition between deformation and dynamic recrystallisation. Grain boundary migration and melt dihedral angle control the bulk rheology. Large and connected melt pockets develop in deformation-dominated systems. At high dihedral angles, small and disconnected melt pockets form in recrystallisation-dominated regimes.